Kindergarten architecture - Anonymous ([S.l.] : Dalian University of Technology Press Co.,Ltd, 2013)
This book describes that the challenge faced in the process of designing a new kindergarten is to create an environment for children in which its function and aesthetic characteristics can exhibit and represent the certain image of children: the ability, good at exploration, proficient in one hundred languages and excellent skills. A kindergarten is not just a place, but also a tool: Every space can be interpreted as an opportunity, where kids can engage in self attempt, knowledge construction and self learning; it can also be interpreted as a laboratory to encourage and support the different processes of childrens growth.
engineering bookfair2015